2019
DOI: 10.1177/0300060519882546
|View full text |Cite
|
Sign up to set email alerts
|

Coronal magnetic resonance imaging of three-dimensional fast-field echo with water-selective excitation improves the sensitivity and reliability of identification of extraforaminal lumbar disc herniation

Abstract: Objective The complete view of the nerve root, including the extraforaminal zone, can be displayed by coronal magnetic resonance imaging (MRI) of three-dimensional (3D) fast-field echo with water-selective excitation (CMRI). However, its sensitivity, specificity, and reliability for the diagnosis of extraforaminal lumbar disc herniation are unclear. We compared the sensitivity, specificity, and reliability of conventional MRI, CMRI, and 3D MRI for the identification of extraforaminal lumbar disc herniation. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Byun et al ( 9 ) observed that the technology could additionally demonstrate the 3D relationship between the nerve root and the intervertebral disc, which is conducive to the discovery of extreme lateral disc herniation. Our previous study confirmed that the sensitivity and specificity of the technique in identifying extreme lateral disc herniation are better than those of conventional MRI ( 10 ). Subsequently, it has also been verified by our other study that the CMRI is beneficial in the differential diagnosis of tumor-like disc herniation ( 5 ).…”
Section: Discussionsupporting
confidence: 77%
“…Byun et al ( 9 ) observed that the technology could additionally demonstrate the 3D relationship between the nerve root and the intervertebral disc, which is conducive to the discovery of extreme lateral disc herniation. Our previous study confirmed that the sensitivity and specificity of the technique in identifying extreme lateral disc herniation are better than those of conventional MRI ( 10 ). Subsequently, it has also been verified by our other study that the CMRI is beneficial in the differential diagnosis of tumor-like disc herniation ( 5 ).…”
Section: Discussionsupporting
confidence: 77%
“…The CMRI scanning parameters were consistent with those used in previous studies 28,29 . Sequence development was performed using a 3.0‐T whole‐body scanner (GE Medical Systems, Chicago, IL) with a spine coil.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid these disadvantages, coronal MRI of threedimensional (3D) fast-field echo with water-selective excitation (CMRI) is considered a non-invasive and reliable novel technology [26][27][28][29] . Byun et al and Shen et al confirmed that CMRI can show the whole length of the nerve root from the origin of the nerve root to the extraforaminal region; the 3D space between the herniated disc and nerve root can also be shown after CMR images are reconstructed without invasive examination 26,27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As early as 2012, Woo Mok Byun discussed the role of 3D MR lumbosacral radiculography in the diagnosis of symptomatic extraforaminal disc herniation [ 9 ]. In our previous studies, CMRI was used to improve the diagnosis of extremely lateral lumbar intervertebral disc herniation and distinguish between lumbar discs mimicking tumor and schwannomas [ 10 , 11 ]. So Hee Park, Sang Woo Kim, and Sartoretti E studied the value of ProSet MR Or CMRI in multiple lumbar foraminal stenosis and foraminal or extraforaminal lesions at L5-S1 [ 19 22 ].…”
Section: Introductionmentioning
confidence: 99%